Demand for technical workforce with industrial major by entrepreneurs in industrial estates - Leekitchwatana, Punnee (Asia-Pacific Journal of Science and Technology, 2017)
This research is aimed to study the demand for vocational and high vocational graduates with industrial major by entrepreneurs under the Industrial Estate Authority of Thailand (IEAT) for both quantity and competency aspects. The tool used in the research is a questionnaire covering the quantity and competency of the graduates. They are validated by experts and are tried out before being used to collect the data. The reliabilities are 0.93 and 0.91 for vocational and high vocational level, respectively. The data was collected from June to August, 2007, and then analyzed by statistics being frequency, percentage, rank, mean, and standard deviation, and it is found that 1) the entrepreneursû demand for graduates with high vocational certificates is high at 71.01%, whereas the demand for graduates with vocational certificates is 28.99%, and 2) the overall demand of the entrepreneurs regarding the competencies of the graduates is at a high level as a whole and for all of 3 domains; affective domain, psychomotor domain, and cognitive domain.